Mitigation of hand-arm vibration in workers on a pneumatic nail gun assembly line - Pan, Yi-Tsong; Chen, Chih-Yong; Chang, Cheng-Ping; Liu, Jen-Chieh; Chen, Hsieh-Ching; Lu, Shih-Yi (Canadian Acoustics, 2011)
Experimental findings and subjective responses of operators’ recruited to assess the effectiveness of the fixture in reducing their hand-arm vibration (HAV) are reported. A wooden fixture was developed to reduce the exposure of assembly line operators to HAV caused by the impact wrench. A wooden fixture, which fastened the impact wrench to a worktable and held the assembly part of nail gun, was designed to reduce the vibration at the operators’ hands by supporting the impact wrench and incorporating shock absorbing polyurethane material. The HAV levels, frequency-weighted root mean square acceleration, with and without the fixture plate were evaluated according to the ISO 5349-1 (2001) and ISO 8041 (2005) standards using Viewlog software. Significant reductions are achieved in frequency- weighted accelerations using the fixture plate. With regards to work efficiency, the design of the fixture requires pans for assembly to be mounted and removed easily and quickly.